Exposure to organic solvents and personality. Issue 1 (1st January 2001) - Chen, R; Dick, F; Semple, S; Seaton, A; Walker, L G
Abstract : OBJECTIVES: Although cognitive and neuropsychological changes have been found after high cumulative exposures to solvents, it is not clear whether such exposures are associated with personality characteristics. To study this two groups of British and Chinese dockyard painters who had been heavily exposed to paint solvents have been investigated. METHODS: 260 Male dockyard painters in the United Kingdom, 539 local community controls, 109 Chinese dockyard painters, and 255 dockyard controls completed the Eysenck personality questionnaire, neuroticism (N) and social conformity or dissimulation (L) scales. The non-parametric Kruskal-Wallis test was used to evaluate differences in scores of personality traits between painters and controls. Adjusted relative risks for painters having high N and L scores were calculated in a Breslow-Cox regression analysis, and exposure-response relations were examined in multivariate logistic regression analysis. Non-parametric Spearman's correlation was used to examine relations between previously determined neuropsychological symptoms and personality. RESULTS: Both British and Chinese data showed that mean neuroticism scores of painters were significantly higher than controls, whereas scores of social conformity did not differ. Relative risk of being a painter increased significantly with increasing N scores, but L scores showed no such trend. In a case-control analysis, there were significant exposure-response relations for the N score. In the United Kingdom the odds ratios (ORs) (95% confidence interval (95% CI), were 2.03 (0.79 to 5.22) for 1–4 years of exposure, 2.38 (0.82 to 6.91) for 5–9 years, 7.05 (1.27 to 39.25) for 10–14 years, and 1.76 (0.63 to 4.89) for 15–41 years. In the Chinese painters, ORs were 4.66 (1.38 to 15.75) for 2–14 years, 10.03 (2.96 to 34.04) for 15–18 years, and 13.56 (3.78 to 48.59) for 19–43 years. Neuroticism was significantly positively related to neuropsychological symptoms in all subjects. Social conformity showed no association with neuropsychological symptoms in British painters and a negative relation among the Chinese painters. CONCLUSION: Increasing symptoms suggesting neuroticism seemed to relate to the duration of painting whereas scores for social conformity and dissimulation did not. The relation between exposure time and response suggests that increased neuroticism may be caused by long term occupational exposure to organic solvents.